Pemeriksaan Kadar Zat Organik Dalam Air Minum Isi Ulang Jenis RO (Reverse Osmosis) - Rahmawati Rahmawati; Dewi Arisanti; Nurhidayat Nurhidayat (Lontara Journal of Health Science and Technology, 2021)
Gallons of refilled drinking water usually don't run out in a single use but run out in a few days or even up to 1 to 2 weeks, depending on usage, and stored at room temperature (27-29 °C). Drinking water that is stored for a long time will allow the growth of microorganisms which are influenced by environmental factors, namely temperature conditions and oxygen supply during storage. This affects the pH and total organic content of drinking water. Inspection of the quality of water products according to the Regulation of the Minister of Health of the Republic of Indonesia Number 492/MENKES/PER/IV/2010, which is a maximum organic matter content of 10 mg/L. According to chemical parameters, drinking water must not contain inorganic and organic substances exceeding the standard with a pH value between 6.5-8.5. The purpose of this study was to determine the levels of organic substances in RO (Reverse Osmosis) refill drinking water. This type of research is a laboratory experiment using purposive sampling technique. The results showed that the average organic content of refilled drinking water with a storage period of 0 days was 1.839 mg/L, 3 days was 2.57 mg/L, and 6 days was 5.28 mg/L. Thus, the levels of organic substances in drinking water are based on storage time of 0, 3, and 6 days using the spectrophotometric method according to the maximum drinking water quality standard.